Metallogenic characteristics of Shitoukengde intrusion and its implications for Ni-Co-(Cu) sulfide mineralization in East Kunlun - Xue-peng Duan; Fan-cong Meng; Zong-qi Wang; Xiao-fei Yu (China Geology, 2024)
ABSTRACT: Xiarihamu deposit is the only super-large Ni-Co deposit found in East Kunlun orogenic belt (EKOB) until present. Shitoukengde (STKD) intrusion is considered to have the potential to become a large Ni-Co deposit in East Kunlun. In order to discuss the metallogenic potential, this study present petrographical, geochemical data, and zircon U-Pb dating for the STKD intrusion. The STKD intrusion is hosted within mafic-ultramafic rocks which contain peridotite, pyroxenite and gabbro, and mainly intruded into the marble of the Paleoproterozoic Jinshuikou Group. Harzburgite and orthopyroxenite are the main country rocks for the Cu-Ni sulfide mineralization. Combine with the positive εHf(t) values (+1.1 to +8.6) of zircons, the enrichment of LILEs, depletion of HFSEs, and lower Ce/Pb ratios of whole rocks indicate that the parental magma was originated from the depleted asthenospheric mantle and experienced 5%–15% crustal contamination. Troctolite formed during the Early Devonian and it has weighted mean 206Pb/238U age of 412 Ma. Regional background information has indicated that the post-collisional extension setting has already existed during the Early Devonian, leading to the formation of STKD intrusion and Cu-Ni sulfide mineralization. STKD intrusion may have the potential to be one economic Cu-Ni sulfide deposit but seems unlikely to be a super-large one.